Endoscopic detection and diagnosis of gastric cancer using image‐enhanced endoscopy: A systematic review and meta‐analysis - Osamu Dohi; Mayuko Seya; Naoto Iwai; Tomoko Ochiai; Junki Yumoto; Hiroki Mukai; Katsuma Yamauchi; Reo Kobayashi; Ryohei Hirose; Ken Inoue; Naohisa Yoshida; Hideyuki Konishi; et al. (DEN Open)
Abstract Objectives We aimed to conduct a systematic review and meta‐analysis to assess the value of image‐enhanced endoscopy including blue laser imaging (BLI), linked color imaging, narrow‐band imaging (NBI), and texture and color enhancement imaging to detect and diagnose gastric cancer (GC) compared to that of white‐light imaging (WLI). Methods Studies meeting the inclusion criteria were identified through PubMed, Cochrane Library, and Japan Medical Abstracts Society databases searches. The pooled risk ratio for dichotomous variables was calculated using the random‐effects model to assess the GC detection between WLI and image‐enhanced endoscopy. A random‐effects model was used to calculate the overall diagnostic performance of WLI and magnifying image‐enhanced endoscopy for GC. Results Sixteen studies met the inclusion criteria. The detection rate of GC was significantly improved in linked color imaging compared with that in WLI (risk ratio, 2.20; 95% confidence interval [CI], 1.39–3.25; p < 0.01) with mild heterogeneity. Magnifying endoscopy with NBI (ME‐NBI) obtained a pooled sensitivity, specificity, and area under the summary receiver operating curve of 0.84 (95 % CI, 0.80–0.88), 0.96 (95 % CI, 0.94–0.97), and 0.92, respectively. Similarly, ME‐BLI showed a pooled sensitivity, specificity, and area under the curve of 0.81 (95 % CI, 0.77–0.85), 0.85 (95 % CI, 0.82–0.88), and 0.95, respectively. The diagnostic efficacy of ME‐NBI/BLI for GC was evidently high compared to that of WLI, However, significant heterogeneity among the NBI studies still existed. Conclusions Our meta‐analysis showed a high detection rate for linked color imaging and a high diagnostic performance of ME‐NBI/BLI for GC compared to that with WLI.